Inconsistent media mediation and problematic smartphone use in preschoolers: Maternal conflict resolution styles as moderators - YANG, Hwajin (Institutional Knowledge at Singapore Management University, 2022)
Previous studies suggest that inconsistent parenting leads to undesired consequences, such as a child's defiant reactance or parent-child conflicts. In light of this, we examined whether mothers' inconsistent smartphone mediation strategies would influence their children's problematic smartphone use during early childhood. Furthermore, given that harsh parenting often escalates a child's behavioral problems, we focused on parent-child conflict resolution tactics as moderators. One hundred fifty-four mothers (ages 25-48 years; M = 35.58 years) of preschoolers (ages 42-77 months) reported their media mediation and parent-child conflict resolution tactics and their child's problematic smartphone use. We found that the positive association between the mother's inconsistent mediation and their child's problematic smartphone use was more pronounced when mothers relied on negative parent-child resolution tactics-i.e., psychological aggression and physical assault. Our findings provide vital theoretical and empirical insights into mother-child relational characteristics for the child's problematic smartphone use.